1989
DOI: 10.1172/jci114166
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and expression of the fibroblast fibronectin receptor in human monocytes.

Abstract: Human monocytes adhere to fibronectin, but the receptor (or receptors) mediating this interaction has not been clearly identified. To examine the nature of this receptor, human monocytes were obtained by counter-current elutriation and were found to adhere to immobilized fibronectin but not to vitronectin or von Willebrand factor. Antibodies and peptides were used to determine whether monocyte adherence to immobilized fibronectin was mediated by a receptor similar to that which mediates the adherence of fibrob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
23
0

Year Published

1991
1991
2006
2006

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(27 citation statements)
references
References 27 publications
4
23
0
Order By: Relevance
“…The CD49e antibody used (BIIG2) was used at a concentration demonstrated to show blocking ofVLA-5 dependent adhesion (21). FN-40 was used at a concentration (100 ug/ml) shown to inhibit binding of VLA-4-positive cells to FN-40-coated plates by 90% (24).…”
Section: Resultsmentioning
confidence: 99%
“…The CD49e antibody used (BIIG2) was used at a concentration demonstrated to show blocking ofVLA-5 dependent adhesion (21). FN-40 was used at a concentration (100 ug/ml) shown to inhibit binding of VLA-4-positive cells to FN-40-coated plates by 90% (24).…”
Section: Resultsmentioning
confidence: 99%
“…Integrins ␣ 4 /␤ 1 (VLA4) and ␣ 5 /␤ 1 (VLA5) are important in the interaction of monocytes with fibronectin (5,10,49). We have previously shown that monocytic phagocytes rely mainly on ␤ 2 -and ␣ 4 -integrins to adhere to the inflamed connective tissue (11).…”
Section: Discussionmentioning
confidence: 99%
“…Cell distribution for each one of these integrins shows a clearly distinct pattern. Thus, VLA-5 is widely distributed (5,8,16), whereas the expression of VLA-3 and VLA-4 is more restricted, the first to adherent cells such as fibroblasts and epithelial cells (5,17), and the second to peripheral blood cells of the monocytic and lymphoid lineages as well as related cell lines (13,16,18).…”
Section: Introductionmentioning
confidence: 99%